Barriers to paramedic professionalisation: a qualitative enquiry across the UK, Canada, Australia, USA and the republic of Ireland - Fintan Feerick; Eoin Coughlan; Shane Knox; Adrian Murphy; Ivan O. Grady; Conor Deasy (BMC Health Services Research)
Abstract Background Paramedicine is undergoing a transformative shift as practitioners seek recognition beyond traditional emergency response roles toward being fully integrated healthcare professionals. Central to this evolution is the process of professionalisation, marked by efforts to expand scope of practice, formalise education and regulation, and achieve greater systemic integration. Despite these developments, significant barriers remain. Purpose This study explores key barriers to the professionalisation of paramedics across five developed healthcare systems, highlighting shared and context-specific challenges. Methods A qualitative study underpinned by a critical theory paradigm was conducted using semi-structured interviews. Over a five-month period (Dec 2022–Apr 2023), 15 expert stakeholders from clinical, educational, policy, and leadership roles in paramedicine and pre-hospital emergency care were recruited across five countries. Interviews were conducted via Microsoft Teams, transcribed verbatim, and analysed thematically with a reflexive and interpretive approach. Results Four main themes were developed: Current Barriers to Expansion– including outdated legislation, inconsistent regulatory frameworks, limited funding, workforce shortages, and insufficient integration within healthcare systems. Elevating Professional Status– focusing on the need for protected titles, standardised education, credentialing, and a stronger professional identity. Impact of COVID-19– participants reflected on the profession’s temporary visibility during the pandemic, followed by policy and funding shifts that diluted that momentum. Future Continuing and Emerging Barriers– encompassing structural and cultural resistance, lack of leadership pathways, and challenges in sustaining innovation and collaboration. Conclusion The study highlights persistent barriers to paramedic professionalisation, including fragmented regulation, uneven educational standards, and systemic underinvestment. Although COVID-19 demonstrated the adaptability and potential of the profession, sustaining progress requires targeted policy reform, stronger regulatory frameworks, investment in education and leadership, and commitment to workforce development. Recognising paramedics as integral healthcare providers is essential to advancing the profession and improving patient care.